EL PAISAJE CARIBEÑO COSTARRICENSE DESDE LA VALORACIÓN INDÍGENA CABÉCAR-TAYNÍ: EL CASO DE LA COMUNIDAD DE GAVILÁN, VALLE LA ESTRELLA, LIMÓN, COSTA RICA - Carballo Chaves, Pablo; Madrigal Herrera, Magdalena (Universidad de Costa Rica, 2019)
In the context of a larger research project on indigenous landscapes in Costa Rica, enrolled in the Universidad de Costa Rica, this article presents an inquiry, centrally theoretical, into the landscape social construction of the indigenous communities of Gavilán (self referred as Cabécar-Tayní), located in Limón. This reflection seeks to understand with a sociological perspective the aesthetic and experiential forms and conceptions within the framework of socio-natural indigenous spaces.